Qualidade de rainhas africanizadas de "Apis mellifera" Linnaeus, 1758 submetidas a condições térmicas e fontes de hidratação em ambiente simulado - Oliveira, Wendy Guadalin de (2025)
The transportation of honey bee queens is an essential strategy for disseminating genetically selected strains, especially given the reduction in colonies associated with laying failures, which can occur due to the stress caused to the queens during poor transportation conditions. This study aimed to evaluate and quantify morphometric and morphophysiological traits, including the weight of ovaries and spermatheca, as well as reproductive quality parameters, in queens, subjected to a simulated transportation environment under various conditions of temperature, humidity, and hydration sources. Ninety fertilized queens from a comercial producer were used in cages adapted from the Benton model. The experimental conditions included three combinations of temperature and relative humidity (12 °C and 48%, 34 °C and 60%, and 38 °C and 70%) and three sources of hydration: control, absorbent cotton soaked in water, and bacterial nanocellulose membranes (NCB) encapsulated with sodium alginate. The queens remained in the respective conditions for three days. The analyses included pre- and post-exposure morphometric measurements, the weight of the ovaries and spermatheca, and an assessment of sperm quality through concentration, motility, and viability. The data was submitted to ANOVA and Tukey's test for statistical comparison. The results showed that heat stress caused by exposure to 34 °C and 60% RH reduced body weight, abdomen length, total length, and the weight of the right and left ovaries. About the sources of hydration, there was a significant difference only in the parameters of sperm motility and viability. We can conclude that heat stress at 34 °C and 60% RH affected the weight, length of the abdomen, and weight of the ovaries, while the different sources of hydration did not alter the morphophysiological traits; however, they contributed to the honey bees' survival. Regarding reproductive quality, only sperm motility was negatively influenced by heat stress.